2008
DOI: 10.1177/1368430207084842
|View full text |Cite
|
Sign up to set email alerts
|

Intraorganizational Respect and Organizational Participation: The Mediating Role of Collective Identity

Abstract: A panel study with two points of measurement throughout a four-month interval (N = 189) in the context of a socio-political organization was conducted to examine the role of collective identity in mediating the relationship between perceived respect and organizational participation. Path analyses confirmed that the effect of perceived respect at Time 1 on organizational participation at Time 2 was fully mediated by the cognitive component of collective identity (`importance-to-identity'). Interestingly, althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 36 publications
2
25
0
Order By: Relevance
“…According to the social identity approach, common group membership induces perceived exchangeability of group members which typically entails expectations of fair and equal, if not favorable, treatment by fellow group members or group authorities (Wenzel 2004). Respectful treatment, which is in accordance with such expectations, is therefore likely give the recipient the signal that he or she is recognized as an equal organization member (''I am treated like them because I am one of them''), thereby intensifying the link between the self and the organization (Emler and Hopkins 1990;Simon et al 2006;Simon and Stürmer 2003;Stürmer et al 2008;Tyler and Smith 1999). Second, fair treatment by organizational authorities also indicates to what extent organization members can take pride in their organization.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…According to the social identity approach, common group membership induces perceived exchangeability of group members which typically entails expectations of fair and equal, if not favorable, treatment by fellow group members or group authorities (Wenzel 2004). Respectful treatment, which is in accordance with such expectations, is therefore likely give the recipient the signal that he or she is recognized as an equal organization member (''I am treated like them because I am one of them''), thereby intensifying the link between the self and the organization (Emler and Hopkins 1990;Simon et al 2006;Simon and Stürmer 2003;Stürmer et al 2008;Tyler and Smith 1999). Second, fair treatment by organizational authorities also indicates to what extent organization members can take pride in their organization.…”
Section: Introductionmentioning
confidence: 95%
“…We grounded our specific hypotheses on the role of social identity concerns in theorizing and research on Tyler and Blader's (2003) group engagement model and conceptually related work (e.g., Ellemers and Boezeman 2010;Simon et al 2006;Stürmer et al 2008). This research brings together insights of the social identity approach (e.g., Turner et al 1987) and the social justice literature (e.g.…”
Section: Introductionmentioning
confidence: 97%
“…Research on community-based renewable energy initiatives revealed that interpersonal and social trust between local people and groups is advantageous for the realization of the projects, as the people feel positive about getting involved and about the development process in general . The identification with the local community is seen as an important determinant for citizens to actively participate and support cooperative behaviors (Stürmer et al, 2008).…”
Section: The Psychological Facets Of Autarky Aspirationmentioning
confidence: 99%
“…Empirical work linking respect and the self indicates that expressions of respect increase self-esteem (Ellemers et al, 2004) and social identification with the collective in which respect is received (Bartel et al, in press;Stürmer et al, 2008). Further, conceptual work also suggests that receiving respect increases individuals' self-esteem, as well as their display of authentic identities (Dutton & Heaphy, 2003).…”
Section: Research Questionmentioning
confidence: 99%
“…In the organizational context specifically, empirical findings suggest that respect has unique and positive effects on organizational participation and identification (Bartel et al, in press;Stürmer, Simon, & Loewy, 2008), and is positively related to in-role and extrarole behaviors (Tyler & Blader, 2002). Van Quaquebeke and Eckloff (2010) found that followers are more likely to identify with a leader, be more receptive to his or her influence, and report higher job satisfaction when they feel respected by the leader.…”
Section: Research On Respectmentioning
confidence: 99%